Keynesian, Non-Keynesian or No Effects of Fiscal Policy Changes? The EMU Case - Bas van Aarle; Harry (ed.) Garretsen (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper studies the experiences with fiscal adjustments in the EuropeanUnion (EU) countries during the transition period to the Economic andMonetary Union (EMU). Using several approaches suggested in the literatureon fiscal adjustments and their macroeconomic effects and in the literatureon EMU, we analyze the effects of the fiscal adjustments during this periodon private consumption. Thereby, we also take the specific context of thetransition towards EMU explicitly into consideration. At best mixed evidencefor the presence of non-linearities in the relation between fiscal adjustmentsand private spending is obtained. There is no clear-cut evidence for thehypothesis of expansionary fiscal contractions which may have alleviatedthe burden from fiscal consolidation in the EMU case. The sensitivity of theresults for a number of factors is also checked.
Keywords: 330; Fiscal Retrenchment; EMU.